Fluorous Molecules for Dye-Sensitized Solar Cells: Synthesis and Characterization of Fluorene-Bridged Donor/Acceptor Dyes with Bulky Perfluoroalkoxy Substituents - Marzari, Gabriela Lorena (2012)
: A series of structurally related sensitizers containing fluorene as a π-conjugated central core have been synthesized, characterized, and applied in the development of dye-sensitized solar cells (DSSCs). The new electron donor (diphenylamine)−acceptor (cyanoacrylic acid) D-π-A molecular structures hold perfluoro-tert-butyl substituents in different positions. It is demonstrated that the fluorous substitution pattern remarkably affects the behavior of dyes as photosensitizers in DSSCs, leading to an improvement in the power conversion efficiencies with respect to analogous nonfluorous molecules.